Linking teaching and research in disciplines and departments (Higher Education Academy (HEA))
This volume is aimed at discipline-based staff who wish to connect their teaching and research roles; those with leadership roles for teaching and for research in departments and intuitions, and for educational developers.

(untitled) - Jenkins, Alan; Healey, Mick; Zetter, Roger (2007)